Aesthetics and Politics in Contemporary Visual Art in El Salvador - Roque Baldovinos, Ricardo (2021)
This article proposes some theoretical tools for understanding contemporary in El Salvador. In the first place, it explains a change to the paradigm of contemporary art after the crisis of the Gallery System, which had been its main space of visibility until the 1990s. In the second place, it attempts to account of the specific political dimension of this art is the El Salvador political and cultural scene.